The poverty impacts of improved soybean technologies in Malawi - Hirpa Tufa, A.; Alene, A.; Manda, J.; Feleke, S.; Assfaw Wossen, T.; Akinwale, M.G.; Chikoye, David; Manyong, Victor (Informa UK Limited, 2021)
Improved soybean varieties and agronomic practices have been widely disseminated to smallholder farmers in Malawi over the last 15 years. However, there is no empirical evidence on the welfare impacts of adopting improved soybean technologies. This paper estimated the poverty impacts of adopting improved soybean technologies using data from 1,234 households in six soybean growing districts accounting for over 80% of the total soybean production in the country. The results from an endogenous switching regression model showed that 32% of the sample households adopted improved soybean varieties and agronomic practices. The adoption benefits were higher for female-headed households and increased with the household head’s education and cultivated land areas. A comparison of the observed and counterfactual incomes for adopters based on the international poverty line of US$1.90 per capita per day showed a 4.16 percentage-point reduction in poverty among the sample households, translating to over 150,000 people lifted out of poverty. The household head’s education level, household size, cultivated land area, livestock size, and asset ownership are associated with the daily per capita income. The results point to the need for scaling up of improved soybean varieties and agronomic practices for greater impacts on poverty reduction among smallholders in Malawi.